Antiapoptotic activity of 30 kDa lipoproteins family from fat body tissue of silkworm, Bombyx mori. (29th September 2014) - Pakkianathan, Britto Cathrin; Singh, Nitin Kumar; König, Simone; Krishnan, Muthukalingan
Abstract The family of 30 kDa lipoproteins (LP1–5) is abundant in silkworm pupa fat body (FB) and hemolymph. One of its members, the 29 kDa protein decreased in concentration from peripheral (PP) FB tissue but was sustained in perivisceral (PV) FB tissue at the time of apoptosis. This study investigated the correlation of the 30 kDa proteins with FB apoptosis. Two protein fractions were purified, a 29 and a 30/31 kDa protein fraction, and they were used to test for activity against actinomycin D‐induced apoptosis in the FB tissues. Concentrations as little as 50 μg/mL of the 29 kDa protein fraction efficiently inhibited apoptosis. Less antiapoptotic activity was detected for the higher MW fraction; DNA fragmentation was observed in FB tissue treated with 50 μg/mL of the 30/31 kDa fraction. The viability of the cells in the 29 kDa protein‐supplemented culture was 40% higher than in the 31 kDa protein‐supplemented culture. However, the 30 kDa lipoproteins were not able to prevent scheduled FB degeneration during silkworm metamorphosis. Thus, it is hypothesized that the antiapoptotic 29 kDa protein needs to be proteolytically degraded by a regulatory mechanism to allow programmed cell death of FB tissue.